A systematic review: an analysis of the promising effects of Myo-inositol and probiotics on the prevention of Gestational diabetes Mellitus - Kamaruddin, Muhammad Aqil; Soe, May Khin Soe; Mazlan, Muhammad Alif Najman; Wan Rishdi, Muhammad Irfan; Ta, Pan Thu (Manuscript Scientific Service, 2025)
Gestational diabetes mellitus (GDM) poses significant health risks for both mothers and infants, and this prevalence of the condition has significantly grown globally, necessitating effective preventive strategies. Myo-inositol and probiotics seem to have potential effects as supplements for GDM prevention. Materials and methods: This systematic review adhered to the PRISMA guidelines. A comprehensive literature search was performed in PubMed, Scopus, Cochrane Library, Science Direct, and Snowball technique was used to enhance the thoroughness of literature search. The retrieved papers were screened separately by two reviewers according to the eligibility criteria, in phases including title, abstract, and full text. The potential for bias in the included papers was evaluated separately by using the critical evaluation checklist from the Joanna Briggs Institute. Data from the included studies were extracted and presented in the table to analysis by the authors. Results: Out of the 311 articles, 11 articles fulfilled our eligibility criterion. Based on inclusion and exclusion criteria, four studies involving myo-inositol reported a significant reduction of GDM occurrence while no studies involving probiotics reported a significant effect of it on GDM prevention. No notable advantages or disadvantages were observed concerning the secondary outcomes, such as complications for both the infant and mother associated with GDM when using myo-inositol and probiotics supplements. Conclusion: A combination of 4 grammes of MI and 400 mg of folic acid (FA) has better beneficial nutrient for preventing GDM when started at around 12-13 weeks of pregnancy and continued until delivery. Although probiotics did not demonstrate preventative benefits on gestational diabetes mellitus GDM, they may have potential impacts on glucose metabolism in pregnant women when lactobacillus acidophilus and bifidobacterium subspecies strains are administered starting at 12-13 weeks of gestation.